Industrial Utilization of Capacitive Deionization Technology for the Removal of Fluoride and Toxic Metal Ions (As3+/5+ and Pb2+). Issue 4 (27th January 2022) - Islam, Md Rabiul; Gupta, Soujit Sen; Jana, Sourav Kanti; Pradeep, Thalappil
Abstract: Capacitive deionization (CDI) is an emerging desalination technology, particularly useful for removing ionic and polarizable species from water. In this context, the desalination performance of fluoride and other toxic species (lead and arsenic) present in brackish water at an industrial scale of a few kilo liters using a CDI prototype built by InnoDI Private Limited is demonstrated. The prototype is highly efficient in removing ionic contaminants from water, including toxic and heavy metal ions. It can remove fluoride ions below the World Health Organization (WHO) limit (1.5 ppm) at an initial concentration of 7 ppm in the input feed water. The fluoride removal efficiency of the electrodes (at a feed concentration of 6 ppm) deteriorates by ≈ 4–6% in the presence of bicarbonate and phosphate ions at concentrations of 100 ppm each. The removal efficiency depends on flow rate, initial total dissolved solids, and other co‐ions present in the feed water. Interestingly, toxic species (As 3+/5+ and Pb 2+ ) are also removed efficiently (removal efficiency > 90%) by this technology. The electrodes are characterized extensively before and after adsorption to understand the mechanism of adsorption at the electrode. Abstract : The desalination performance of fluoride and other toxic species (lead and arsenic)‐contaminated brackish water using a capacitive deionization prototype built by InnoDI Private Limited is demonstrated. The removal efficiency depends on the flow rate, total dissolved solids, and other ions present in the feed water.